2018
DOI: 10.3846/20294913.2016.1233515
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a Network Evaluation Framework for Improving the Financial Ecosystem in Small-Medium Size Firms

Abstract: Abstract. This study presents an evaluation framework to measure the various operations to acquire the optimal core operation (CO) when financier provides the supply chain finance (SCF) services in smartphone industry supply chain (SC). The proposed model applies the modify Delphi method and analytic network process (ANP). First, the evaluation model establishes a network with three criteria, eleven sub-criteria and four operations. Next, the ANP is utilized to the framework to obtain the relative weights of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…At the traditional level, SCM aims to comprehensively manage all aspects of the entire SC (e.g., suppliers, manufacturers, and distributors) to meet the customers' needs. Moreover, it works through each link in the SC, including purchasing, material management, manufacturing, distribution, and marketing, to reduce costs and maximize profits for all supply members while improving cooperation among SC partners in terms of goods, infor-mation, and capital flows [40][41][42][43]. Furthermore, R. W. Seifert and D. Seifert [44] considered traditional SCM as 'physical supply chain management', also known as PSCM.…”
Section: Conceptual Development Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…At the traditional level, SCM aims to comprehensively manage all aspects of the entire SC (e.g., suppliers, manufacturers, and distributors) to meet the customers' needs. Moreover, it works through each link in the SC, including purchasing, material management, manufacturing, distribution, and marketing, to reduce costs and maximize profits for all supply members while improving cooperation among SC partners in terms of goods, infor-mation, and capital flows [40][41][42][43]. Furthermore, R. W. Seifert and D. Seifert [44] considered traditional SCM as 'physical supply chain management', also known as PSCM.…”
Section: Conceptual Development Analysismentioning
confidence: 99%
“…Meanwhile, the upstream/downstream players, and financial institutions, are also important SC components. Banks and banking systems are primarily referred to as financial institutions in this phase [1,27,42,50]. According to the credit support from the CO of '1' in the SC and through the control of the four flows of 'business', 'logistics', 'capital', and 'information', the financing credit support for 'N' of the upstream and downstream partners (particularly for SMEs) is completed (see Figure 7).…”
Section: Conceptual Development Analysismentioning
confidence: 99%
“…However, AHP still has the feature that the level and criteria must be independent in decision evaluation, and subsequent studies have broken through the independent features and introduced the concept of network to improve evaluation efficiency. Hence, Saaty (1996) proposed the now widely used analytic network process (ANP) to solve the independence assumption of AHP [53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…Azzi et al proposed a new type of supply chain network collaboration planning model and found that the total profit level of supply chain nodes is positively correlated, and the two-way collaborative green supply chain is optional [2]. Lin CS and Lin CY use a multistage Stackelberg game method to study the green procurement relationship between manufacturers and suppliers in the supply chain and effectively reduce suppliers' carbon emissions [3]. Lin CS and Lin CY studied the asymmetric duopoly model of two competing supply chains under different carbon emission technologies and encouraged the use of clean energy technologies to reduce carbon emissions [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Lin CS and Lin CY use a multistage Stackelberg game method to study the green procurement relationship between manufacturers and suppliers in the supply chain and effectively reduce suppliers' carbon emissions [3]. Lin CS and Lin CY studied the asymmetric duopoly model of two competing supply chains under different carbon emission technologies and encouraged the use of clean energy technologies to reduce carbon emissions [3,4]. Papert and Pflaum study the production and emission reduction decision-making problems of an order-based supply chain composed of manufacturers and retailers under the constraints of the capital market and trade market [5].…”
Section: Introductionmentioning
confidence: 99%